Accelerated VB 2008 - Fouché, Guy (Apress, 2012)
Visual Basic 2008 (VB 2008) is relatively easy to learn for anyone familiar with another object-oriented language. Even someone familiar with Visual Basic 6.0 who is looking for an object-oriented language will find VB 2008 easy to pick up. However, though VB 2008, coupled with .NET, provides a quick path for creating simple applications, you still must know a wealth of information and understand how to use it correctly in order to produce sophisticated, robust, fault-tolerant applications. We teach you what you need to know and explain how best to use your knowledge so that you can quickly develop true VB 2008 expertise. Idioms and design patterns are invaluable for developing and applying expertise, and we show you how to use many of them to create applications that are efficient, robust, fault-tolerant, and exception-safe. Although many are familiar to C++ and Java programmers, some are unique to .NET and the Common Language Runtime (CLR). We show you how to apply these indispensable idioms and design techniques to seamlessly integrate your VB 2008 applications with the .NET runtime, focusing on the new capabilities of VB 2008